The design of a low-noise rotor-only axial flow fan series - Van der Spuy, Sybrand Johannes (Stellenbosch : University of Stellenbosch, 2012)
ENGLISH ABSTRACT: A design routine was derived for designing a series of rotor-only axial flow fans. The routine was applied by designing two different series of axial flow fans. The first design was for a general application rotor-only axial flow fan. This fan series was designed, built and tested in co-operation with Howden Air Industries for both research and commercial purposes. The second design was for a low-noise fan series, which was designed, built and tested by the University of Stellenbosch for research purposes only. The design theory used the principle of blade cropping, meaning that one blade was designed to fit all the different fan sizes. The fan series was designed for diameters ranging from 3 15 mm to 1000 mm. The fan rotors were designed to conform to a velocity profile of minimum exit kinetic flux. The general application fan design was concentrated around the popular fan diameter sizes of 500 rnm, 560 mm and 630 mm and a rotor speed of 1440 rpm, using a commercially available fan series as reference. The low-noise fan design concentrated on one fan size only, namely 630 mm, while also making use of the principle of forward blade sweep. The remaining fan design principles stayed the same as for the general application fan design. The F-series airfoils were used as blade sections for both fan designs. Both fan series were tested for fan noise and performance in accordance with the BS 848 Standards part 1 (1980) and 2 (1985). A selection of fan diameter sizes was tested for the general application fan to verify its perfo!"mance over a range of fan sizes. This indicated a fan series with a wide range of efficient operation, including excellent noise characteristics. A 630 mm diameter fan was used to test the low-noise fan series. It showed both high efficiency and low noise characteristics. The reduction in fan noise achieved with the low-noise fan does not justi1)' the amount of work and costs involved in the designing process, compared to the general application fan.